Contest pieces for trombone and piano - Rousseau, Samuel 1853-1904; Pfeiffer, Georges Jean 1835-1908; LaNux, Paul Véronge de; Bachelet, Alfred 1864-1944; Guilmant, Alexandre 1837-1911; Saint-Saëns, Camille 1835-1921 (A-R Special Publications, 2015)
A collection of pieces composed for students of the Paris Conservatoire